1995
DOI: 10.1172/jci117760
|View full text |Cite
|
Sign up to set email alerts
|

Role of the low density lipoprotein receptor in the flux of cholesterol through the plasma and across the tissues of the mouse.

Abstract: These studies were undertaken to quantify cholesterol balance across the plasma space and the individual organs of the mouse, and to determine the role of the low density lipoprotein receptor (LDLR) in these two processes. In the normal mouse (129 Sv), sterol was synthesized at the rate of 153 mg/d per kg body weight of which 78% occurred in the extrahepatic tissues while only 22% took place in the liver. These animals metabolized 7.1 pools of LDL-cholesterol (LDL-C) per day, and 79% of this degradation took p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
190
1
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(203 citation statements)
references
References 57 publications
9
190
1
3
Order By: Relevance
“…Previous studies have shown that in mice, ϳ80% of LDL is degraded in liver, mostly via the LDL receptor pathway (50).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that in mice, ϳ80% of LDL is degraded in liver, mostly via the LDL receptor pathway (50).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a gross phenotype in TPC2 À / À mice on SD is not surprising, since SD contains relatively little cholesterol (r0.02% w/w). On this diet, the cholesterol requirement of the animals is achieved primarily through de novo biosynthesis 38 .…”
Section: Articlementioning
confidence: 99%
“…The intake of cholesterol per day on this diet is approximately 20-30 times above the amount an average animal synthesizes to maintain homoeostasis when its dietary needs are not being met 38 . The average liver weight/body weight ratio of TPC2 À / À on CD was significantly increased compared with WT on CD (Fig.…”
Section: Articlementioning
confidence: 99%
“…Knocking out the genes coding for the LDL receptor or apoE does not appear to be associated with any major functional abnormalities in the brain of the mouse. 39,40 However, in aged apoE knockout mice, there is a lipid deposition in astrocytes in specific brain areas. 41 Deletion of the genes coding for the very low-density lipoprotein receptor and the apoE receptor 2 results in a highly significant phenotype, with a defect in the neuronal layering, 42 whereas deletion of either of the 2 genes alone has much less effect.…”
Section: Transport Of Cholesterol Within the Brainmentioning
confidence: 99%